PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNIVERSITAS BINA NUSANTARA ANGKATAN 2006 UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Panggabean, Rosinta Ria; Kusumaningsih, Nana Wulansari (Bina Nusantara University, 2011)
This study aimed to determined whether motivation affects students of accounting and double programs to determine whether there were differences between the accounting student with double programs to follow PPAk. There are four hypotheses proposed, the first three hypotheses are tested using multiple linear regression method, whereas the fourth hypotheses is tested using independent t-test of the two samples with 95% confidence level (Î±=0.05). The result of this study have several implications for various parties related to the PPAk. From the findings obtained in this study, the quality and career motivation variables have significant impact on student interest in follow PPAk. But the career variable is the most significant factor affecting student interests to follow PPAk, while the motivation of economic variables does not significantly affect the interest to follow PPAk. In addition, for the last hypothesis there is no differences between student interest in accounting and double program students. This can be caused by accounting student and double programs student have studied multiple courses in accounting subjects of the course provides knowledge about the field.Â